925. GRIFFITHARIA HEDLUNDII. (8th February 2020) - Rushforth, Keith
Summary: Griffitharia hedlundii (C.K. Schneider) Rushforth (syn. Sorbus hedlundii C.K. Schneider) is illustrated. Its distribution and ecology is reported. The synonyms are listed and described. Instructions for its cultivation are given.